1994
DOI: 10.2307/1243745
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Emerging Technologies Under Output Uncertainty

Abstract: A model of divisible technology adoption under incomplete information dissemination and output uncertainty is developed. We identify economic and subjective factors affecting technology adoption and its intensity. Empirical estimation employs a mixed dichotomous‐continuous framework with nonrandom sample selection. Producers' adoption intensity is conditional on their knowing about and deciding to adopt the new technology. Using survey data on bST (bovine somatotropin) adoption among Texas dairy producers, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(61 citation statements)
references
References 12 publications
2
56
0
3
Order By: Relevance
“…In this work, we consider three components of human capital: formal education, work experience and knowledge of the institutional environment acquired through experience with past policies and/or programmes. Theories of managerial efficiency and learning-by-doing imply that years of formal education have a positive impact on firm growth in general (Variyam and Kraybill, 1994;Barkham, 1994), while past experience with schemes has been found to influence the producerÕs willingness to adopt new methods of production, new inputs, or adopt new marketing strategies (Saha et al, 1994;Dimara and Skuras, 2003a;Dimara et al, 2003). A growing body of literature in economic sociology stresses that markets are socially structured institutions, infused with cultural norms and meaning (Lie, 1997).…”
Section: Producersõ Evaluations Of Quality Cues: a Theoretical Modelmentioning
confidence: 99%
“…In this work, we consider three components of human capital: formal education, work experience and knowledge of the institutional environment acquired through experience with past policies and/or programmes. Theories of managerial efficiency and learning-by-doing imply that years of formal education have a positive impact on firm growth in general (Variyam and Kraybill, 1994;Barkham, 1994), while past experience with schemes has been found to influence the producerÕs willingness to adopt new methods of production, new inputs, or adopt new marketing strategies (Saha et al, 1994;Dimara and Skuras, 2003a;Dimara et al, 2003). A growing body of literature in economic sociology stresses that markets are socially structured institutions, infused with cultural norms and meaning (Lie, 1997).…”
Section: Producersõ Evaluations Of Quality Cues: a Theoretical Modelmentioning
confidence: 99%
“…Few studies have actually considered these decisions jointly. Saha et al (1994) focused on the role of incomplete information in the adoption of bovine somatropin by a sample of farmers in Texas. Due to differences in natural resources, political and socioeconomic conditions, the importance of factors affecting the joint decisions to acquire information and adopt new innovations differ across countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the effect is higher with the matched sample, providing additional evidence that samples may differ before pre-processing. Previous research has shown that large operations tend to be less risk averse than small operations (Saha, Love, and Schwart, 1994;Saha, Shumway, and Talpaz, 1994;Koundouri et al, 2009). This result indicates that both efficient irrigation and perennial crops are used as risk reducing investments by small operations.…”
Section: Bivariate Probit Results Of the Decision To Adopt Conservatimentioning
confidence: 99%
“…However, previous literature has found that farm size is a significant predictor of risk attitudes, with farm size negatively correlated with risk aversion (Saha, Love, and Schwart, 1994;Koundouri et al, 2009). When separating relative and absolute risk aversion, Saha, Shumway, and Talpaz (1994) found that small farms have higher absolute risk aversion and lower relative risk aversion than large farms.…”
Section: Land Ownership Informationmentioning
confidence: 90%